Pull-out strength comparison of a novel expanding fastener against an orthopaedic screw in an ovine vertebral body: an ex-vivo study - Oldakowski, M.; Oldakowska, I.; Kirk, T.; Ford, Chris; Sercombe, T.; Hardcastle, P.; Day, R. (2016)
© 2016 Taylor & Francis The purpose of this study was to mechanically test a novel Unthreaded Expandable Fastener (UEF), manufactured using Selective Laser Melting, which was designed for fixation in the cervical lateral mass. The pull-out strength and stiffness of the prototype UEFs was evaluated in a non-osteoporotic ovine bone model against equivalent screws. The prototype UEF demonstrated a 41% increase in failure force and a 60% reduction in failure force standard deviation compared to the screws. All bone samples were micro CT-scanned and no significant differences in bone microstructural properties was found between the screw and UEF sample sets, indicating that the UEFs may be less sensitive to bone quality variation. This increased performance can potentially translate into improved surgical outcome and reduced surgical risk for lateral mass fixation. With further design optimisation, additional improvement in performance over screws may be possible in future studies.